Assessing pre-service history teachers' pedagogical content knowledge with a video survey using open-ended writing assignments and standardized rating items. Issue 1 (30th April 2019) - Waldis, Monika; Nitsche, Martin; Wyss, Corinne
Abstract : This paper explores pre-service history teachers' ability to recognize and reflect on typical situations occurring in the history classroom and to link these to students' historical learning. Therefore, we draw on the concept of professional vision (Goodwin, 1994), which assumes that teachers need a professional knowledge base to monitor and to reason about teaching and student learning. Based on theoretical notions of teachers' pedagogical content knowledge (PCK), we investigated history teachers' professional vision by means of a video survey with integrated video clips, open-ended writing assignments and standardized item ratings. We collected data from 303 and 220 pre-service teachers at the beginning and at the end, respectively, of their subject-specific teacher training. The collected data open up the possibility of 'simultaneous triangulation' (Morse, 1991), which was used for test validation. First, we tested the reliability of the closed-ended test instrument using item response theory, in order to develop a feasible test model. Second, we investigated the validity of the test instrument by comparing test results with the findings of the open-ended writing task. In general, student teachers reached rather low test scores. They experienced difficulties in assessing classroom events in terms of their potential to support historical competencies and to evaluate the consequences for students' learning. Findings from the open writing assignment show that student teachers commented largely on generic teaching strategies while hardly noticing student learning. In sum, the chosen methodological approaches seem to contribute to a more distinct picture of preservice teachers' abilities to reason about history teaching and learning.